2017
DOI: 10.4038/tar.v28i4.8239
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on irrigation water demand of paddy: a case study from <i>Hakwatuna Oya</i> irrigation scheme in Sri Lanka

Abstract: Assessment of irrigation water requirement (IWR) is a prerequisite for planning and management of an irrigation scheme, particularly for a water short scheme. In this context, this study was conducted to estimate the current and future IWR under A2 (very heterogeneous world) and B2 (world in which emphasis is on local solutions to economic, social, and environmental sustainability) scenarios of IPCC emission for Hakwatuna Oya irrigation scheme using SDSM and CROPWAT models. It was found that the reference evap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The high evaporation rates have greatly decreased the water levels and availability, and high runoff rates have likewise affected water levels, water availability, flood vulnerability, and drought in the study area. Unfortunately, research about climate change's impact on surface water resources in Sri Lanka has shown similar results (Withanachchi et al, 2014;Rajendram, Gunewardena & Rajendram, 2017). Studies such as Bonjean Stanton et al, (2016), Alahacoon & Edirisinghe, (2021), and Weerasinghe et al, (2018) reveal that the authors' water sources' evaporation rates directly affect water resources when studying future climate change.…”
Section: Future Rainfall Changes Of the Northern Region Of Sri Lanka ...mentioning
confidence: 96%
“…The high evaporation rates have greatly decreased the water levels and availability, and high runoff rates have likewise affected water levels, water availability, flood vulnerability, and drought in the study area. Unfortunately, research about climate change's impact on surface water resources in Sri Lanka has shown similar results (Withanachchi et al, 2014;Rajendram, Gunewardena & Rajendram, 2017). Studies such as Bonjean Stanton et al, (2016), Alahacoon & Edirisinghe, (2021), and Weerasinghe et al, (2018) reveal that the authors' water sources' evaporation rates directly affect water resources when studying future climate change.…”
Section: Future Rainfall Changes Of the Northern Region Of Sri Lanka ...mentioning
confidence: 96%
“…Rice is the staple food crop in Sri Lanka and around 1.8 million farmers are involving in paddy cultivation, island wide. The demand for rice is increasing day by day and in the year 2020 it is expected to reach by 35 % (De Silva et al, 2007;Rajendran et al, 2017). Yet there is a controversy as to whether the high Cd level in the dry zone regions of Sri Lanka is a possible causative factor for CKDu.…”
Section: Heavy Metal Contamination and Accumulationmentioning
confidence: 99%
“…However, Mullaitivu is categorized as Sri Lanka's highest poverty index district. After the war, heavy crop damages were recorded due to weather extremes, especially drought (Rajendram et al, 2017). This continued every year after the end of the war.…”
Section: Introductionmentioning
confidence: 99%